Evaluation of the synergistic antifungal activity of Elettaria cardamomum extract in combination with Amphotericin B, Clotrimazole, and Ketoconazole against oral Candida species: an in vitro study - P. S., Devika; Anna Sajan, Ierene; Athulya, S.; Kumar K. S., Harish (International Journal of Research in Medical Sciences, 2026)
Background: The growing incidence of antifungal resistance in Candida species presents a major clinical concern, highlighting the need for alternative therapeutic strategies. This study aimed to evaluate the synergistic potential of Elettaria cardamomum extract (ECE) in combination with conventional antifungals-amphotericin B, clotrimazole, and ketoconazole - against oral Candida isolates, to enhance antifungal efficacy. Methods: A cross-sectional study was conducted from June 2024 to June 2025, including 161 clinical isolates of Candida species obtained from oral cavity. Identification was performed using standard mycological techniques. Antifungal susceptibility testing of ECE alone and in combination with standard drugs was carried out using the checkerboard microbroth dilution method. Fractional Inhibitory Concentration Index (FICI) were calculated to interpret the type of interaction - synergy, additive, indifference, or antagonism and statistical analyses compared susceptibility profiles between clinical isolates and control strain. Results: ECE significantly potentiated the activity of azole antifungals, particularly ketoconazole, across all Candida species. The ketoconazole and ECE combination showed the highest synergy in C. albicans, with additive or synergistic interactions also observed in C. tropicalis and P. Kudriavzevii. Clotrimazole and ECE exhibited additive to moderate synergy, while amphotericin B and ECE combinations were largely indifferent or antagonistic. Clinical isolates exhibited higher MICs and lower synergy compared to control strains, indicating resistance trends. Conclusions: ECE combined with imidazole antifungals demonstrated promising synergistic or additive activity, suggesting potential benefits such as reduced dosage, minimized toxicity, and delayed resistance. Further studies on phytochemical profiling, optimized formulations, and in vivo validation are warranted to support clinical application.